2010
DOI: 10.3109/09537104.2010.512402
|View full text |Cite
|
Sign up to set email alerts
|

Statins have an early antiplatelet effect in patients with acute myocardial infarction

Abstract: Statins confer an antiplatelet effect in hypercholesterolemic subjects and in stable coronary artery disease patients. We explored the antiplatelet effects of statins in ST-elevation myocardial infarction (STEMI) patients undergoing primary angioplasty. Of 120 STEMI patients, 80 (67%) received statins while 40 (33%) did not. Ex vivo platelet reactivity was studied on admission and 72 hours later by conventional aggregometry and under flow conditions (Impact R). Measures of platelet reactivity under flow condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…In an experimental model of acute thrombosis induced in the carotid artery, Obi et al 30 demonstrated that intravenous infusion of lovastatin significantly reduced thrombosis by hampering platelet adhesion to the carotid lesion. Human studies confirmed these findings after 3 to 7 days of treatment with statins, 31,32 with the small inhibition of serum cholesterol that occurred after 3 days not fully supporting a direct antiplatelet effect by statins. To address this question, we measured several markers of platelet activation as early as 2 hours after administration of 40 mg of atorvastatin in hypercholesterolemic patients.…”
Section: Statins and Platelet Activationsupporting
confidence: 70%
“…In an experimental model of acute thrombosis induced in the carotid artery, Obi et al 30 demonstrated that intravenous infusion of lovastatin significantly reduced thrombosis by hampering platelet adhesion to the carotid lesion. Human studies confirmed these findings after 3 to 7 days of treatment with statins, 31,32 with the small inhibition of serum cholesterol that occurred after 3 days not fully supporting a direct antiplatelet effect by statins. To address this question, we measured several markers of platelet activation as early as 2 hours after administration of 40 mg of atorvastatin in hypercholesterolemic patients.…”
Section: Statins and Platelet Activationsupporting
confidence: 70%
“…The PRISM trial (Platelet Receptor Inhibition in Ischemic Syndrome Management) demonstrated a better outcome of ACS patients when they were on statins in the first month after the event, which is unlikely to be caused by remodeling processes of the plaque in such a short timeframe and are rather to be explained by reduced platelet activation and/or attenuated coagulation system. It was observed that statins have an early inhibitory effect on platelets of patients with AMI showing reduced aggregation after challenge with collagen and a markedly lower platelet surface adhesion in vitro (Matetzky et al, 2011). …”
Section: Statinsmentioning
confidence: 99%
“…Statin therapy has been associated with lower urinary thromboxane levels, 70 a marker of activated circulating platelets, and reduced ex vivo shear-induced platelet activation. 71 However, not all studies have found an effect of statins on platelet function. 72 …”
Section: Role Of Platelet Biology In Device-induced Injurymentioning
confidence: 99%